The Islamic Religious Education in the Post Truth Era - Alza Nabiel Zamzami Alza; Dely Tresia Putri; Mahfud Junaedi (The Future of Education Journal, 2024)
The rapid development of technology and social media in the post-truth era has led to the distortion of facts and the spread of unverified information, including in the realm of religious understanding. Islamic Religious Education (PAI) is faced with a major challenge in remaining relevant amidst the flood of disinformation and hoaxes that affect public religious understanding. This study aims to analyze how PAI can play a role in addressing the challenges of the post-truth era. This research uses a qualitative method with a library research approach. The analysis is carried out in three stages: data condensation, data presentation, and conclusion drawing. The results indicate that PAI must teach the importance of tabayyun (information verification), critical thinking, and instill values of honesty and responsibility in responding to information circulating on social media. PAI also plays a role in strengthening digital literacy so that the younger generation is not easily swayed by emotional and manipulative narratives that have the potential to mislead. Islamic Religious Education can become an important instrument in building a society that is critical and firmly adheres to the truth.